PENGARUH VOUCHER GRATIS ONGKOS KIRIM DAN LIVE STREAMING TERHADAP IMPULSIVE BUYING PADA PENGGGUNA TIKTOKSHOP DI KOTA PASURUAN - Rozaq, Mohammad Alfian; Pudyatiningsih, Agnes Ratna; Erwantiningsih, Eni (Yayasan Education and Social Center, 2025)
The development of digital technology has shifted consumer behavior from conventional to online shopping, one of which is through the Tiktok Shop platform. This study aims to analyze the influence of free shipping vouchers and live streaming on impulsive buying among Tiktok Shop users in Pasuruan City, both simultaneously and partially. The research employs a quantitative approach with purposive sampling technique. The sample consists of 96 Tiktok Shop users who have made at least two purchases. Data analysis was conducted using multiple linear regression with the assistance of spss. The result indicate that simultaneously, free shipping vouchers and live streaming have a significant effect on impulsive buying (F-value = 73.184 with significance = 0.000). Partially, both variables also exhibit a positive and significant influence, with live streaming (t-value = 11.180) having a greater impact compared to free shipping vouchers (t-value = 2.947). The coefficient of determination (R2) of 0.611 indicates that 61.1% of the variation in impulsive buying is influenced by these two variables. These findings demonstrate that digital promotion strategies, such as free shipping vouchers and live streaming, effectively enhance impulsie buying tendencies among consumers. The study provides practical implication for e-commerce player in formulating effective marketing strategies.